Framing and reframing R2P—a responsibility to protect humanity from evil. Issue 6 (18th September 2020) - Royer, Christof
ABSTRACT: This article takes issue with de-politicised and moralistic conceptions of the Responsibility to Protect (R2P) and, inspired by the political theory of Hannah Arendt, develops a 're-politicised' and 'de-moralised' account of R2P. It argues that by relying on a link between a moral responsibility to 'save strangers' and practical political action, R2P turns a blind eye to the political interest of powerful actors. And by trying to transform R2P into a 'blueprint', 'roadmap' or 'emergency plan' for political action, many commentators try to render obsolete political deliberation and practical judgement on a case-by-case basis. The present article argues that it is necessary to develop a more realistic view of R2P's role and potential in world politics. R2P, it is argued, has an important discursive function and considerable potential to influence and guide international decision-making processes. Drawing on Arendt's conception of 'evil' as a crime against humanity itself, this article reframes R2P as a 'responsibility to protect humanity from evil'. An Arendtian understanding of mass atrocities as crimes against our common humanity (i.e. as evils) facilitates the development of a re-politicised and de-moralised account of R2P: This account recognises its discursive role, it actively seeks to generate political interest for action in the face of harrowing mass atrocities but also acts as a leash on intervention in less severe cases. Abbreviation R2P: Responsibility to Protect; UN: United Nations; NATO: North Atlantic Treaty Organisation; ICISS: International Committee on Intervention and State Sovereignty